Antimicrobial Activities of Some Thyme (Thymus, Staureja, Origanum and Thymbra) Species against ImportantPlant Pathogens - Kizil, Suleyman; Uyar, Fikret (Asian Journal of Chemistry, 2010)
Different types of plants are used as thyme, such as Tyhmbra, Origanum, Satureja, Thymus and Coridathymus in various regions of the world. In the present study, essential oil components of Thymus kotschyanus, Satureja hortensis, Origanum onites and Thymbra spicata were determined by GC and antimicrobial and antifungal activities of essential oils of these plants against four plant pathogens were evaluated at concentrations of 5, 10 and 15 μg and incubation times of 24, 48 and 72 h. The major components of the essential oils determined by GC were thymol (41.6%) in Thymus kotschyanus, carvacrol in Origanum onites (40.7%), Satureja hortensis (20.6%) and Thymbra spicata (81%). Aqueous and hexane extracts of each plant were tested for their antibacterial activity by using agar disk diffusion method. The results indicated that all essential oils exhibit antibacterial activity against Clavibacter michiganensis subsp. michiganensis, Pseduomonas syringae pv. tomato and Macrophomina phaseoli, except Xanthomonas campestris pv. malvacearum. In addition, it has been observed that gram +ve bacteria are more sensitive than gram –ve bacteria.